SDG WORKS ON ENDING POVERTY IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
Pakistan needs to take a multifaceted approach to achieving SDG 1, which includes advancements in social protection, healthcare, education, employment, and gender equality. Although the government and citizens are working on a number of projects, Pakistan's economic limitations and development gaps make combating poverty there still extremely difficult. However, there is potential for significant progress in lowering poverty and enhancing the standard of living for Pakistan's citizens through targeted investments, improved governance, and inclusive policies. This research paper emphasis on a thorough framework for addressing poverty in Pakistan is offered by the SDGs. Implementing policies that support equitable and sustainable development will require ongoing efforts from the government, foreign partners, and local communities in order to meet these aims.